John Dryden’s The Rival Ladies and Cervantes’s Las dos Doncellas: A Comparative Study - González, Raquel Serrano (Jordan Journal of Modern Languages & Literatures, 2023)
John Dryden’s The Rival Ladies (1664) is a stage adaptation of Las dos doncellas (The Novel of the Two Maidens) (1613), an exemplary novel written by the celebrated author Miguel de Cervantes. Produced in a context where the identity categories upholding Spain’s social orthodoxy were facing increasing resistance, Las dos doncellas offers a bounteous source to explore the fixity of gender, as it features two cross-dressed ladies who travel across a disrupted nation unhesitant to wield their ‘manly’ swords. This article analyses Dryden’s re-positioning of the source text into a new cultural-ideological context, also marked by the unsettling of hegemonic gender narratives and the resulting power structures. The playwright capitalises on the subversive potential of the source text, which is rendered wider and more multifaceted by the genre shift, to engage with the ideological milieu of Restoration England. The study also examines some scenes of Dryden’s own invention which address issues of pervasive concern to the target culture, mainly gender identities, roles and relations. Significantly, his additions to Cervantes’ plot denounce social constraints on female freedom, such as forced marriages and the double sexual standard.